Children and Pre-Adolescents' Moral Disengagement and Cooperation in the Context of Deprived Neighborhoods: An Action Research Project - Roberto Marcone; Deborah Brancaccio; Vincenza Borghese; Lucia Ariemma; Giuseppe Ritella (MDPI AG, 2024)
The purpose of this study is to examine family-level and community-level factors contributing to children and pre-adolescents' moral disengagement and cooperation in the context of deprived neighborhoods. A set of validated measures has been administered to 374 participants, who were involved in an action research project aimed at reducing cultural disadvantage in a deprived Italian neighborhood. The analysis was conducted through descriptive and correlational analyses. In addition, a model was tested through a path analysis. The findings are consistent with the hypothesized model and allow us to discuss the role of parental rejection, age and socioeconomic status in the examined developmental processes.